Characterization of Edge Contact: Atomically Resolved Semiconductor–Metal Lateral Boundary in MoS2. Issue 41 (18th September 2017) - Kwon, Hyeokshin; Lee, Kiyoung; Heo, Jinseong; Oh, Youngtek; Lee, Hyangsook; Appalakondaiah, Samudrala; Ko, Wonhee; Kim, Hyo Won; Jung, Jin‐Wook; Suh, Hwansoo; Min, Hongki; Jeon, Insu; et al.
Abstract: Despite recent efforts for the development of transition‐metal‐dichalcogenide‐based high‐performance thin‐film transistors, device performance has not improved much, mainly because of the high contact resistance at the interface between the 2D semiconductor and the metal electrode. Edge contact has been proposed for the fabrication of a high‐quality electrical contact; however, the complete electronic properties for the contact resistance have not been elucidated in detail. Using the scanning tunneling microscopy/spectroscopy and scanning transmission electron microscopy techniques, the edge contact, as well as the lateral boundary between the 2D semiconducting layer and the metalized interfacial layer, are investigated, and their electronic properties and the energy band profile across the boundary are shown. The results demonstrate a possible mechanism for the formation of an ohmic contact in homojunctions of the transition‐metal dichalcogenides semiconductor–metal layers and suggest a new device scheme utilizing the low‐resistance edge contact. Abstract : The edge contact and the lateral boundary between a semiconducting layer and a metalized interfacial layer are investigated using scanning tunneling microscopy/spectroscopy and scanning transmission electron microscopy techniques. The electronic properties and the energy band profile across the boundary are shown. A new device scheme based on the low‐resistance edge contact is thus provided.